1963
DOI: 10.1111/j.1748-1716.1963.tb02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Reactions of the Cutaneous Vessels to Cold Exposure

Abstract: FOLKOW, B., K. H. Fox, J. KROG, H. ODELRAM and 0. THoRks. Studies on the reactions of the cutaneous vessels to cold exposure. Acta physiol. scand. 1963. 58. 342-354. -Some inter-relationships between the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 16 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…That in the range between 7 and 11 0C small oscillations in temperature imposed during stimulation of the sympathetic nerves result in large oscillations in contractile response can be attributed to the fact that minimal changes in the amount of noradrenaline released are amplified markedly by the augmented responsiveness of the vascular smooth muscle cells. Earlier work on isolated arteries, as well as in the intact organism, showed that precapillary cutaneous vessels usually fail to respond to noradrenaline at 5 C (Keatinge, 1958;Folkow, Fox, Krog, Odelram & Thoren, 1963;Patton & Wallace, 1978), although strong direct myogenic activation still can cause a certain degree of contractile activity (Keatinge, 1964). The reason for the different behaviour between arteries and veins is uncertain, but it probably reflects the different ways in which cutaneous arterial and venous smooth muscle handle activator Ca2+, with the former relying more on the influx ofextracellularly available ions than the latter (Vanhoutte, 1976;Vanhoutte, Verbeuren & Van Nueten, 1980).…”
Section: Unstimulated Preparationsmentioning
confidence: 99%
“…That in the range between 7 and 11 0C small oscillations in temperature imposed during stimulation of the sympathetic nerves result in large oscillations in contractile response can be attributed to the fact that minimal changes in the amount of noradrenaline released are amplified markedly by the augmented responsiveness of the vascular smooth muscle cells. Earlier work on isolated arteries, as well as in the intact organism, showed that precapillary cutaneous vessels usually fail to respond to noradrenaline at 5 C (Keatinge, 1958;Folkow, Fox, Krog, Odelram & Thoren, 1963;Patton & Wallace, 1978), although strong direct myogenic activation still can cause a certain degree of contractile activity (Keatinge, 1964). The reason for the different behaviour between arteries and veins is uncertain, but it probably reflects the different ways in which cutaneous arterial and venous smooth muscle handle activator Ca2+, with the former relying more on the influx ofextracellularly available ions than the latter (Vanhoutte, 1976;Vanhoutte, Verbeuren & Van Nueten, 1980).…”
Section: Unstimulated Preparationsmentioning
confidence: 99%
“…It has previously been suggested that such a cold-induced ''indirect'' vasoconstriction is orchestrated either by the reflex response to a noxious stimulus and/or the action of a central mechanism excited by the cold blood returning from the skin (Folkow et al, 1963;Kregel et al, 1992;Pickering, 1932). The increased adrenal secretion triggered by the prolonged cold application constitutes an additional mechanistic explanation to the phenomenon (Freeman, 1935).…”
Section: Temperature Response Of the Non-immersed Regionsmentioning
confidence: 99%
“…17 Studies measuring tissue oxygen tension in nonfreezing cold injury models have demonstrated hypoxia and local tissue anoxia, both subcutaneously and intramuscularly, during cooling. 7,23 Cold injury is also known to reduce blood flow, induce vasopressor changes, 8 increase the viscosity of the blood, 24 and cause platelet aggregation. 10,33 It has also been pointed out that, although hypothermia reduces the rate of cellular metabolism, the poor perfusion of capillaries results in insufficient oxygen being released to meet the needs of surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%